Lipophilic extracts of Leucas zeylanica, a multi-purpose medicinal plant in the tropics, inhibit key enzymes involved in inflammation and gout. (5th October 2018) - Napagoda, Mayuri; Gerstmeier, Jana; Butschek, Hannah; Lorenz, Sybille; Kanatiwela, Dinusha; Qader, Mallique; Nagahawatte, Ajith; De Soyza, Sudhara; Wijayaratne, Gaya Bandara; Svatoš, Aleš; Jayasinghe, Lalith; Koeberle, Andreas; et al.
Abstract: Ethnopharmacological relevance: Leucas zeylanica (L.) W.T. Aiton is a popular, multi-purpose medicinal plant in Sri Lanka but the pharmacological potential and the chemical profile have not been systematically investigated to understand and rationalize the reported ethnobotanical significance. Aim of the study: The present study was undertaken to scientifically validate the traditional usage of this plant for the treatment of inflammatory conditions, gout and microbial infections. Inhibition of 5-lipoxygenase (5-LO), microsomal prostaglandin E2 synthase (mPGES)−1 and xanthine oxidase (XO) by different extracts of L. zeylanica was investigated to determine the anti-inflammatory and anti-gout activity, respectively. The antibacterial and antifungal activities were also studied and the relevant constituents in the bioactive extracts were tentatively identified. Materials and methods: Cell-free and/or cell-based assays were employed in order to investigate the effects of the extracts against the activity of human 5-LO, mPGES-1 and XO as well as to assess antioxidant properties. The antibacterial activity of the extracts was determined by the broth micro-dilution method against Gram positive and Gram negative bacteria including methicillin-resistant Staphylococcus aureus while the agar dilution method was employed to determine the anti- Candida activity. Gas chromatography coupled to mass spectrometric (GC-MS) analysis enabled the characterization of secondary metabolites in the extracts. Results: The dichloromethane extract of L. zeylanica efficiently inhibited 5-LO activity in stimulated human neutrophils (IC50 = 5.5 µg/mL) and isolated human 5-LO and mPGES-1 (IC50 = 2.2 and 0.4 µg/mL). Potent inhibition of XO was observed by the same extract (IC50 = 47.5 μg/mL), which is the first report of XO-inhibitory activity of a Sri Lankan medicinal plant. Interestingly, significant radical scavenging activity was not observed by this extract. Only the n -hexane extract exhibited antibacterial activity against Staphylococcus aureus and Staphylococcus saprophyticus with a MIC of 250 µg/mL while the anti- Candida activity was moderate. GC-MS analysis revealed the presence of phytosterols, fatty acids, sesquiterpenes, diterpenes and several other types of secondary metabolites. Conclusions: Potent inhibition of 5-LO, mPGES-1 and XO rationalizes the ethnopharmacological use of L . zeylanica as anti-inflammatory and anti-gout remedy. Interestingly, the antimicrobial activities were not prominent, despite its wide utility as an antimicrobial medication. Graphical abstract: fx1